2017
DOI: 10.1186/s12906-017-2047-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salvia miltiorrhiza extract with supplemental liquefied calcium on osteoporosis in calcium-deficient ovariectomized mice

Abstract: BackgroundExtracts from Salvia miltiorrhiza Bunge have been used in traditional Asian medicine to treat coronary heart disease, chronic renal failure, atherosclerosis, myocardial infraction, angina pectoris, myocardial ischemia, dysmenorrheal, neurasthenic insomnia, liver fibrosis and cirrhosis. The aim of the study was to investigate the anti-RANK signal effect of the combination of S.miltiorrhiza Bunge (SME) and liquefied calcium (LCa) supplement with ovariectomized (OVX-SML) mice, a osteoporosis animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Studies have shown increased serum levels of ALP in OVX rats (Park et al. 2017 ); in our study, FAEE treatment tended to reduce ALP levels in serum. Those data indicate that FAEE can inhibit the bone turnover in OVX rats.…”
Section: Discussionsupporting
confidence: 64%
“…Studies have shown increased serum levels of ALP in OVX rats (Park et al. 2017 ); in our study, FAEE treatment tended to reduce ALP levels in serum. Those data indicate that FAEE can inhibit the bone turnover in OVX rats.…”
Section: Discussionsupporting
confidence: 64%
“…For our in vivo study, OVX-induced osteoporosis in mice was selected as a bone repair model because it has been widely used to evaluate the bone formation of bioactive molecules and biomaterials in bones (41, 42). After treatment with AG for 4 weeks, bone histomorphometric analysis and micro-CT analysis were used to measure the effect of AG on bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, Nich et al () showed that OPG mRNA expression was not significantly different between OVX mice and OVX mice treated with E2 groups. Park et al () reported that Salvia miltiorrhiza extract increased the serum OPG levels without affecting serum E2 levels. Therefore, we suggest the mechanism responsible for the anti‐osteoporotic effects of PCE17 observed in OVX mice is partly different from that of estrogen.…”
Section: Discussionmentioning
confidence: 99%